柴油机卷簧扭振减振器力学模型和性质研究 - 田中旭; 陈俊豪; 蔡正祥; 汪俊; 李嘉鹏 (Jixie qiangdu)
Owning high reliability and excellent performance,sleeve spring-type torsional vibration dampers is often used in high-power marine diesel engine to reduce torsional vibration.However,since sleeve spring pack belongs to the large deformation and nonlinear problem of the superposed curved beam,the description of the deformation state,the change of the contact area and the limitation of the surrounding space on the deformation make the study of mechanical model very complicated.So far,there still isn’t an efficient and accurate computational method for the stiffness parameters.Therefore,the computational model of the stiffness for the dampers was studied.Based on the superposed curved beam bending models,these complex factors such as the contact between the springs,support and limit of stroke limiter were fully considered.A complete damper stiffness mechanics model and related algorithms were presented and program was made as well.Correctness of the model was verified by the method of finite element analysis.Based on this,the influence of the main design parameters of the damper on the mechanical properties was studied,which provided a basis for design of the damper.